Welfare analysis using nonseparable models - Stefan Hoderlein; Anne Vanhems (Centre for Microdata Methods and Practice (cemmap), 2010)
This paper proposes a framework to model empirically welfare effects that are associated with a price change in a population of heterogeneous consumers. Individual demands are characterized by a nonseparable model which is nonparametric in the regressors, as well as monotonic in unobserved heterogeneity. In this setup, we first provide and discuss conditions under which the heterogeneous welfare effects are identified, and establish constructive identification. We then propose a sample counterpart estimator, and analyze its large sample properties. For both identification and estimation, we distinguish between the cases when regressors are exogenous and when they are endogenous. Finally, we apply all concepts to measuring the heterogeneous effect of a chance of gasoline price using US consumer data and find very substantial differences in individual effects.
Keywords: 330; Welfare; Consumer Surplus; Price Effect; Nonseparable Model; Nonparametric; Quantile; Endogeneity; Compensating Variation; Konsumentenrente; Preis; Wohlfahrtsanalyse; Nichtparametrisches Verfahren